"We didn't forget" Utilizing a Community‐Nurse Partnership to Promote Health in Rockport, Texas after Hurricane Harvey. Issue 1 (11th November 2019) - Salt, Rebekah J.; Sickora, Cindy; Page, Tracey L.; Martinez, Martha L.; Cantu, Adelita G.; Schwab, Karen W.; Lee, Moonju
Abstract: Background: On August 25th 2017 Harvey, a category 4 hurricane, made landfall on the south coast of Texas with heavy winds and rain that severely damaged the seaside town of Rockport. The challenge facing healthcare providers following a natural disaster is timely assessments of community need and available resources. One week later, faculty at the University of Texas Health Science Center San Antonio, School of Nursing (SON) completed a community assessment and developed valuable partnerships. Aims: Eighteen days after the initial assessment, faculty had secured support from The Children's Health Fund and operationalized strategies to provide disaster relief and experiential learning opportunities for the SON Population Focused Health undergraduate students. Materials & Methods: The community‐as‐partner model served as the framework to apply the nursing process to a community in crisis. As the focus shifted to recovery, the team prioritized the need to address long‐term consequences for children after a natural disaster. Results: Two educational sessions were designed using an interactive and instructional approach to discuss parental strategies to assess and support children as they navigated through loss after Harvey. Discussion: This community‐nurse partnership has endured, and the SON faculty and students continue to travel to Rockport to promote health and provide education to the community.